Additive Manufacturing With Soft TPU – Adhesion Strength in Multimaterial Flexible Joints - Harris, Conor G.; Jursik, Nicholas J. S.; Rochefort, Willie E.; Walker, Travis W. (Frontiers in Mechanical Engineering, 2019)
The adhesion in 3D-printed composites between dissimilar layers was investigated in response to demand for multimaterial prints. Previously, we reported on the thermal properties for printability of thermoplastic polyurethane (TPU) blends~\cite{harris001}. Here, we report the qualitative and quantitative adhesion properties between commonly-printed materials, acrylonitrile butadiene styrene (ABS) or acrylonitrile styrene acrylate (ASA), and flexible TPU. ASTM D1002/D3164 lap shear adhesion tests were performed to measure the adhesion strength between the acrylonitrile plastics and TPU, finding values of $4.7~MPa$ between ABS and TPU and $6.4~MPa$ between ASA and TPU. These values are on the same order of magnitude of reported commercial adhesives, suggesting that multimaterial 3D printing can provide an automated, industrially-relevant alternative to handmade fabrication. SEM images are reported to show the quality of adhesion between materials in the composites. These images expose qualitative differences in the interlayer adhesion between materials in the composites that depend on the order of printing. Thermal (DSC and TGA) and rheological characterizations were performed to investigate the processing conditions of the extruded plastics while they are in their melt states. The role of viscosity is shown to have major implications on the adhesion, as materials with lower viscosities displayed improved filling of the interlayer voids and increased strength of adhesion.